The effect of cold water immersion on 48-hour performance testing in collegiate soccer players - Rupp, K. A.; Selkow, N. M.; Parente, W. R.; Ingersoll, C. D.; Weltman, A. L.; Saliba, S. A. (The Journal of Strength and Conditioning Research, 2012)
This randomized, controlled, laboratory study was designed to examine the effect of cold water immersion (CWI) as a recovery modality on repeat performance on the yo-yo intermittent recovery test (YIRT), a widely accepted tool for the evaluation of physical performance in soccer, separated by 48 hours. Twenty-two healthy Division I collegiate soccer players (13 men and 9 women; age, 19.8 ± 1.1 years; height, 174.0 ± 9.0 cm; mass, 72.1 ± 9.1 kg) volunteered as participants during the noncompetitive season. The YIRT was used to induce volitional fatigue and was administered at baseline and again 48 hours later. Athletes progressively increased sprint speed between markers set 20 m apart until pace was failed. Countermovement vertical jump (CMVJ) was used to assess anaerobic power and was measured before YIRT, immediately post-YIRT, and 24 and 48 hours post-YIRT. A 10-cm horizontal visual analog scale was administered immediately, 24 hours and 48 hours post-YIRT to assess perceived fatigue (PF) in the legs. Participants were randomly placed into the CWI or control group. The CWI condition consisted of immersion to the umbilicus in a 12°C pool for 15 minutes, whereas the control group sat quietly for 15 minutes. There were no significant differences between intervention conditions on YIRT performance (control, 4,900 ± 884 m; CWI, 5,288 ± 1,000 m; p = 0.35) or PF (control, 9.4 ± 0.5 cm; CWI, 9.3 ± 0.6 cm; p = 0.65) at 48 hours post-YIRT. There was a main time effect for CMVJ over 48 hours, but no group differences (pre-YIRT, 64.6 ± 11.0 cm; post-YIRT, 66.4 ± 10.9 cm; 24 hours post-YIRT, 63.4 ± 9.9 cm; 48 hours post-YIRT, 63.1 ± 9.4 cm; p = 0.02). This study demonstrated that in collegiate soccer players, CWI performed immediately and 24 hours after induced volitional fatigue did not affect subsequent physical performance estimates.